2018
DOI: 10.1111/ctr.13346
|View full text |Cite
|
Sign up to set email alerts
|

More severe deficits in functional status associated with higher mortality among adults awaiting liver transplantation

Abstract: The impact of functional status on liver transplant (LT) waitlist outcomes is not well studied. Early evidence suggests frailty portends increased mortality. We aim to evaluate the association of functional status with LT waitlist survival and the probability of receiving LT among adults with cirrhosis. Using 2005-2016 United Network for Organ Sharing (UNOS) data, we retrospectively assessed the association of functional status, as determined by Karnofsky Performance Status Score (KPSS) with LT waitlist surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…( 3,4 ) Frailty is present in 18% to 25% of patients with end‐stage liver disease (ESLD), and it is associated with nearly twice the mortality of reference populations as well as increased hospital admission, waitlist mortality, posttransplant complications, and health care costs. ( 3,5‐7 ) Frailty is also a progressive condition for patients on the waiting list as its prevalence doubles from the time of listing to the time of LT. ( 8,9 )…”
mentioning
confidence: 99%
“…( 3,4 ) Frailty is present in 18% to 25% of patients with end‐stage liver disease (ESLD), and it is associated with nearly twice the mortality of reference populations as well as increased hospital admission, waitlist mortality, posttransplant complications, and health care costs. ( 3,5‐7 ) Frailty is also a progressive condition for patients on the waiting list as its prevalence doubles from the time of listing to the time of LT. ( 8,9 )…”
mentioning
confidence: 99%
“…As a modifiable risk factor, poor functional status (FS) is associated with higher liver transplant (LT) waitlist mortality independent of model for end-stage liver disease (MELD) by a variety of metrics, including Karnofsky performance status score (KPSS) which is an accurate, validated subjective tool in assessing FS as a measure of frailty in patients on the LT waitlist. [1][2][3][4][5] However, whether FS alone is directly causative of higher risk of mortality or whether the impact of FS on waitlist mortality is mediated through other factors is not well understood.…”
mentioning
confidence: 99%
“…We have demonstrated that children with Medicaid insurance undergoing first‐time isolated liver transplantation have worse outcomes compared to patients with other insurance. Clinical parameters such as renal function, portal vein thrombosis, poor functional status, location in the hospital at the time of transplant, or previous abdominal surgery have been well described as leading to the worst outcomes post‐liver transplantation 8‐12 . Significant emphasis is placed on optimizing these clinical parameters in the perioperative period in order to have excellent post‐transplant outcome.…”
Section: Discussionmentioning
confidence: 99%